Electromagnetic shielding effectiveness of carbon fibre reinforced composites. (15th September 2019) - Munalli, D.; Dimitrakis, G.; Chronopoulos, D.; Greedy, S.; Long, A.
Abstract: This paper reports results on the shielding effectiveness parameter of laminated epoxy composites with carbon fibre reinforcements. Measurements of shielding effectiveness were carried out with a coaxial transmission line testing chamber according to ASTM 4935 standard and epoxy-matrix composites with continuous carbon-fibres were proven to be an excellent electromagnetic interference shielding material, where a composite slab made of 4 layers of prepregs provided more than 99.9% of electromagnetic attenuation. It was found that the reflection mechanism of the shielding material was mainly influenced by the fibre volume ratio, and that an increase in the number of layers of the composite resulted in higher shielding effectiveness due to a greater absorption mechanism. Calculations of the shielding effectiveness parameter of the material used were made by means of commercial electromagnetic simulation tools, having determined experimentally the overall resistivity of the composite. The findings presented in this work suggest that in presence of a greater number of interfaces at different impedance the separate modelling of matrix and fibres at mesoscopic scale must be taken into account.